EARTHQUAKE FAILURES ON BUILDINGS AND THE ROLE OF ARCHITECT ON BUILDING SAFETY - Noor Cholis Idham (Dimensi: Journal of Architecture and Built Environment, 2018)
The safety of building users against earthquakes is not directly caused by earthquakes, but rather by the ability of the people and environment to deal with the shake. The failure of the building is the most causing factor for the casualties and property losses. However, the building structural strength is not the single decisive aspect of building safety but also accompanying by others such as building design and the use of architectural elements. This paper explores the various failures after earthquakes and its relationship with architecture designs as the work of architect in the building process. The discussion is conducted based on the type of the failures, the causing factor of the damages, and how the builders should anticipate it. The results of this study show that the main principles relating to the safety of buildings are closely related to architects who play a significant role in building design starting from the decision of the location, choosing the appropriate building type, designing less vulnerable structure, and avoiding the complexity in building design. Architects are expected to increase the safety of building users by their devoted responsibility for avoiding the unnecessary casualties.